Особливості правової регламентації економічної активності населення України в умовах сьогодення - Кобко, Р. В.; Kobko, R. V. (Південноукраїнський правничий часопис. - 2023. - № 3. - С. 108-113, 2023)
Визначено сучасний стан правової регламентації економічної активності населення України в умовах правового режиму воєнного стану. Аргументовано необхідність вдосконалення нормативно-правової бази у сфері підприємницької діяльності.

The article examines the legal nature of economic activity of the population and the relevance of improving bylaws on employment of the population. The purpose of the article is to determine the peculiarities of the legal regulation of the economic activity of the population of Ukraine under conditions of the legal regime of martial law. The article examines the provisions of current legislation of Ukraine on the mentioned issues and defines the argumentation of the need to improve the regulatory and legal framework in the field of entrepreneurial activity. The article begins with a discussion of the problem of the definition of "economic activity of the population" in legal science and an analysis of the essence of the concept of economic activity of the population within the framework of groups of normative legal acts as sources of civil, economic and labor law. The author analyzed the latest research and publications, as well as defined directions for future research in this area. The article analyzes the provisions of the current Law of Ukraine ‘On Employment of the Population’ and the Order of the State Statistics Committee of Ukraine ‘On Approval of Methodological Provisions on the Classification and Analysis of the Economic Activity of the Population’, which also belong to the acts of these groups. The paper proposed to consider the improvement of the legal regulation of the economic activity of the population in the sphere of modernization of the private sector of the economy as a leading segment of the national economy, which contributes to the transformation of the entrepreneurship system during martial law in Ukraine. Factors and characteristics affecting the legal regulation of the economic activity of the population under modern conditions of martial law in Ukraine are analyzed. One of the central provisions of the article is the thesis that modern jurisprudence lacks a single doctrinal approach to defining the concept of "legal regulation of economic activity of the population." The article concludes that normative documents on employment of the population in Ukraine are considered to be inconsistent with modern realities, are extensive and are not seen as contributing to the modernization and effective functioning of the private sector of the economy.

Определено современное состояние правовой регламентации экономической активности населения Украины в условиях правового режима военного положения. Аргументирована необходимость усовершенствования нормативно-правовой базы в сфере предпринимательской деятельности.
Peculiarities of psychological barriers in police professional activity
Keywords: економічна активність населення; economic activity of the population; экономическая активность населения; воєнний стан; martial law; военное положение; підприємницька діяльність; entrepreneurship; предпринимательская деятельность; правова регламентація; legal regulation; правовая регламентация; правосуб’єктність; legal personality; правосубъектность; зайнятість населення; population employment; занятость населения